Vitamin D in pediatric patients with obesity and arterial hypertension - Živa Radulović (Nature Portfolio, 2021)
Abstract The purpose of this study was to find potential differences in vitamin D levels between different groups: overweight children with hypertension, normal-weight children with hypertension, overweight children with normal blood pressure and normal-weight children without hypertension, representing the control group. We also wanted to determine whether there are correlations between vitamin D levels and other clinical laboratory parameters, to evaluate the potential need for substitution. We measured vitamin D, homocysteine, total cholesterol, HDL, LDL, triglycerides, uric acid, glucose, apolipoprotein A1, apolipoprotein B, alkaline phosphatase, calcium, phosphate and magnesium serum levels in all groups. We also took anthropometric measurements (body weight, height, body mass index (BMI)) and observed patients’ blood pressure. The results were analyzed with SPSS statistic tool with basic statistical methods. The study included 175 children between 5 and 18 years of age. Fiftyseven were healthy (group A—control group), 41 normal-weight with hypertension (group B), 44 overweight with hypertension (group C) and 33 overweight with normal blood pressure (group D). The results showed statistically significant differences in values of vitamin D between all groups—A and B (p = 0.003), A and C (p < 0.001), A and D (p < 0.001), B and D (p = 0.043), B and C (0.030), except for groups C and D (p = 0.830). There were statistically significant correlations between vitamin D and BMI (r = − 0.196, p = 0.010), systolic pressure (r = − 0.190, p = 0.002), diastolic pressure (r = − 0.149, p = 0.050), homocysteine (r = − 0.208, p = 0.007), triglycerides (r = − 0.196, p = 0.011) and apolipoprotein A1 (r = 0.222, p = 0.007), confirmed in multivariate model. For the blood pressure, the higher the systolic blood pressure, the lower the average vitamin D was. The pilot study shows significant differences in serum vitamin D levels between all groups of children, apart from groups C and D. These results, combined with statistically significant correlations between vitamin D and systolic and diastolic blood pressure suggest the need for monitoring and potential substitution of vitamin D in in pediatric patients with hypertension.